Intelligent Decision Technologies 2017 Proceedings of the 9th KES International Conference on Intelligent Decision Technologies (KES-IDT 2017) - Part II (Smart Innovation, Systems and Technologies,, 2018)
The volume presents a collection of peer-reviewed articles from the 9th KES International Conference on Intelligent Decision Technologies (KES-IDT-17), held in Vilamoura, Algarve, Portugal on 21-23 June 2017. The conference addressed critical areas of computer science, as well as promoting knowledge transfer and the generation of new ideas in the field of intelligent decision making, project management and data analysis. The range of topics addressed includes methods of classification, prediction, data analysis, decision support, modeling, social media and many more in such diverse areas as finance, linguistics, management and transportation.